Tradisi “Marhaban” dalam Perspektif Maqashid Syari’ah: Studi Kasus di Semurup Kabupaten Kerinci - Dinarti, Yetri; Zainal Azwar (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This study aims to further understand how the “marhaban” tradition is carried out in Semurup, Kerinci Regency. The focus is to what extent the “marhaban” tradition meets or may conflict with the principles of maqashid sharia. This study is an empirical study with a descriptive qualitative approach. Through this field research, the author will try to explore primary data sourced from the relevant place, namely in Semurup, Kerinci Regency. Data collection techniques are carried out by interview and observation. The data analysis techniques used include data reduction and classification, data presentation, and conclusion. The results of the study show that the “marhaban” tradition is carried out by completing the Qur'an first, dhikr, and prayers, strengthening family relationships, and maintaining cultural identity by involving community members and there is no waste or unnecessary expenditure in its implementation to maintain balance and justice in the management of the property. Parents also get inner peace because they feel they have started their children's lives with the blessings and protection of Allah.